1962
DOI: 10.1086/190077
|View full text |Cite
|
Sign up to set email alerts
|

Brightness Distribution in Discrete Radio Sources. III. The Structure of the Sources.

Abstract: The visibility functions of 195 radio sources are interpreted in terms of the structure of these -sources. Of the 195 sources, 174 are known or presumed to be extragalactic. Seventy-five of these extragalactic sources are resolved with the interferometer spacings used, and complex structure is found i n all but 13. In the sources showing complex structure, two similar components with nearly equal intensities are found in 15, 40 show two or more components of unequal intensities, while 7 appear to be a bright c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1968
1968
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…The present resolution is not sufficient to estimate the angular extent of this region. This source is of high brightness temperature (Maltby and Moffet 1962). The extensive variation of integrated polarization with wavelength (Gardner and Davies 1966b) suggests the presence of internal depolarization.…”
Section: Pks1648+05 (Hercules A): Figure 15mentioning
confidence: 94%
“…The present resolution is not sufficient to estimate the angular extent of this region. This source is of high brightness temperature (Maltby and Moffet 1962). The extensive variation of integrated polarization with wavelength (Gardner and Davies 1966b) suggests the presence of internal depolarization.…”
Section: Pks1648+05 (Hercules A): Figure 15mentioning
confidence: 94%
“…It was used mainly at frequencies from 960 MHz to a few GHz. Studies by Maltby and Moffet (1962) and Fomalont (1968) illustrate the use of this instrument for measurement of intensity distributions, an example of which is shown in Fig. 1.14.…”
Section: Measurements Of Intensity Profilesmentioning
confidence: 99%
“…In the meantime the Caltech Interferometer [13] had also found that many sources had complex structures. All of these early observations used model fitting to measured visibility curves, but it wasn't until synthesis techniques were used that convincing images of radio sources were obtained.…”
Section: Aperture Synthesis Imagingmentioning
confidence: 99%